Gut bacterial communities in black soldier fly larvae Hermetia illucens from different rearing locations using metagenomic and culture-dependent approaches - PONGPAN PHUENGMUN; KAMONRAT SUWANCHAISRI; JARIYA RODDEE; JUREEMART WANGKEEREE (Society for Indonesian Biodiversity, 2026)
Abstract. Phuengmun P, Suwanchaisri K, Roddee J, Wangkeeree J. 2026. Gut bacterial communities in black soldier fly larvae Hermetia illucens from different rearing locations using metagenomic and culture-dependent approaches. Biodiversitas 27 (1): d270123. https://doi.org/10.13057/biodiv/d270123. The black soldier fly larva (BSFL; Hermetia illucens) has gained increasing attention as an alternative protein source for animal feed. Knowledge of its gut bacterial communities is critical for ensuring microbial safety and utilization in rearing systems. In this study, BSFL samples were collected from six different rearing locations, and their gut microbiota were characterized using both 16S rRNA amplicon sequencing (V3-V4 region) and culture-dependent techniques. Twelve amplicon libraries were constructed from pooled samples corresponding to different rearing sites. After quality filtering, the number of clean reads ranged from 73,108 to 75,871 sequences, and clustering of these reads yielded between 98 and 717 operational taxonomic units (OTUs). Alpha diversity indices, including Shannon (3.51-6.07), Simpson (0.82-0.97), and Chao1 (98.04-717.00), indicated that the BSFL gut harbored a diverse and dynamic bacterial community, with variation in microbial richness and evenness. The most abundant phyla were Proteobacteria, Firmicutes, and Bacteroidota. At the genus level, dominant taxa commonly detected included Dysgonomonas, Proteus, Enterococcus, Klebsiella, and Providencia. Among the detected taxa were potentially pathogenic bacteria, such as Campylobacter. Through culture-dependent analysis, 57 bacterial isolates belonging to Proteobacteria and Firmicutes were identified by 16S rRNA gene sequencing. The most frequently cultured genera included the foodborne pathogen Bacillus cereus, along with other species such as Bacillus amyloliquefaciens and Priestia megaterium. This study represents the first investigation of BSFL gut bacterial communities from multiple locations in Thailand integrating metagenomic and culture-dependent approaches. The findings expand current knowledge of BSFL gut bacterial communities and highlight important biosafety considerations. In addition, identifying gut-derived bacterial isolates represent promising candidates for further evaluation of their beneficial roles in improving BSFL rearing efficiency.